Ecological impact of changes in intrinsic growth rates of species at different trophic levels. Issue 4 (21st February 2022) - Selaković, Sanja; Säterberg, Torbjörn; Heesterbeek, Hans
Abstract : Decreased and increased intrinsic growth rate and abundance of a single species can severely and negatively impact other species in the same food web. Here we compare the wider system effects of decreased and increased intrinsic growth rates of species occupying different trophic levels. Specifically, we derive the change in growth rate of a single (focal) species necessary to cause a 90% reduction in the abundance – a quasi‐extinction – of another species in model communities. We find that even relatively small changes, negative as well as positive, in the growth rate of the focal species can cause quasi‐extinctions of others. Furthermore, the magnitude of change needed to cause a quasi‐extinction depends on the trophic level of the perturbed species. The potential ecosystem impact of such 'negative' and 'positive' changes is largely unknown. We argue that such a targeted decrease or increase could be induced by human interference, such as hunting or harvesting, but also by an outbreak or fade‐out of an infectious disease. As ecosystems maintain many and diverse infectious agents, these results suggest that these agents may play an important role in the structure and balance of ecosystems.